2016
DOI: 10.4250/jcu.2016.24.4.278
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Utility of Echocardiography for the Diagnosis and Prognosis in Children with Bronchopulmonary Dsyplasia

Abstract: BackgroundBronchopulmonary dysplasia (BPD) may result in chronic pulmonary artery hypertension and right ventricular (RV) dysfunction. Various echocardiographic assessments of RV dysfunction have been used to determine whether echocardiographic measurements of premature infants with BPD could provide sensitive measures of RV function that correlates with BPD severity.MethodsTwenty-eight control subjects without BPD (non BPD group), 28 patients with mild BPD, 11 patients with moderate BPD, and six patients with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 34 publications
(47 reference statements)
0
8
0
Order By: Relevance
“…Choi et al found that preterm BPD patients without evidence PVD/PH may nevertheless have RV dysfunction between 35 and 37 weeks PMA. 36 Haque et al found similar results using myocardial deformation imaging in a cohort of BPD patients without PH. 37 The current paradigm of BPD suggests that preterm infants with BPD may have impairments in the growth, structure and function of the pulmonary vasculature which may lead to PH and ultimately RV dysfunction.…”
Section: Discussionmentioning
confidence: 65%
“…Choi et al found that preterm BPD patients without evidence PVD/PH may nevertheless have RV dysfunction between 35 and 37 weeks PMA. 36 Haque et al found similar results using myocardial deformation imaging in a cohort of BPD patients without PH. 37 The current paradigm of BPD suggests that preterm infants with BPD may have impairments in the growth, structure and function of the pulmonary vasculature which may lead to PH and ultimately RV dysfunction.…”
Section: Discussionmentioning
confidence: 65%
“…1,[21][22][23] Previous echocardiography studies have found BPD to have a detrimental impact on cardiac function at or near term corrected gestational age, 4,6,7,12,24-26 early infancy 5,8,11,13,14 and school age. 27 Most studies have found alterations in RV function 4,6,7,[11][12][13][14]24 while few have performed prospective longitudinal echocardiography analysis 4,12,13,26 or have examined LV function. 5,8,26 Due to the presence of ventricular interactions it is relevant to include a biventricular analysis.…”
Section: Discussionmentioning
confidence: 99%
“…In BPD, right ventricular dysfunction is common and associated with adverse outcomes and the left ventricular (LV) function is characterized by abnormal diastolic but preserved systolic function by conventional analysis. [2][3][4][5][6][7][8] These early abnormalities may contribute to longer-term cardiovascular disease related morbidity and mortality. 9,10 Newer echocardiographic methods such as myocardial deformational imaging have been demonstrated to be more sensitive than conventional methods in detecting changes in cardiac function, 3,6,11,12 potentially allowing for improved detection and targeted intervention in at-risk infants.…”
Section: Introductionmentioning
confidence: 99%
“…There are several parameters to evaluate RV dysfunction, in this issue of the journal, Choi et al,2) tissue Doppler imaging (TDI)-myocardial performance index (MPI) is used to evaluate RV dysfunction in BPD. Previous studies showed difference in TDI across various BPD severities with pulmonary hypertension.…”
mentioning
confidence: 99%
“…The current research by Choi et al2) represent that RV TDI-MPI may be useful method for early detection of RV dysfunction without pulmonary hypertension in BPD and it is necessary to study the incidence and severity of future pulmonary hypertension accordance with value of RV TDI-MPI.…”
mentioning
confidence: 99%